Logistic regression analysis to identify factors contributing to stunting cases - Khikmah, Laelatul; Yulianto, Safaat (Institute of Computer Science (IOCS), 2025)
Stunting is a condition characterized by impaired growth and development in children, caused by various factors such as poor nutrition, infections, and a lack of psychosocial stimulation. Indonesia is one of the Asian countries with a high prevalence of stunting. The increasing stunting rates have raised concerns about the nation's future generation. The aim of this study is to identify the factors contributing to stunting cases, particularly in Karangtengah Village, Sumberjo Village, Kumpulrejo Village, Kutoharjo Village, Krajankulon Village, and Sarirejo Village in Kaliwungu Subdistrict, Kendal Regency, using a logistic regression approach. The variables in this study include stunting status as the dependent variable, while the independent variables are gender, low birth weight (LBW), child disease history, marital status, maternal education, maternal height, pregnancy status, ANC history, maternal phone usage duration, maternal anemia history, child intake and nutrition, and hygiene and environmental conditions. Based on the analysis results, it was found that only the duration of maternal phone usage significantly influenced the occurrence of stunting in children, with a tendency value of 0.071.